2017
DOI: 10.1186/s12933-017-0567-x
|View full text |Cite
|
Sign up to set email alerts
|

Joint analysis of left ventricular expression and circulating plasma levels of Omentin after myocardial ischemia

Abstract: BackgroundOmentin-1, also known as Intelectin-1 (ITLN1), is an adipokine with plasma levels associated with diabetes, obesity, and coronary artery disease. Recent studies suggest that ITLN1 can mitigate myocardial ischemic injury but the expression of ITLN1 in the heart itself has not been well characterized. The purpose of this study is to discern the relationship between the expression pattern of ITLN1 RNA in the human heart and the level of circulating ITLN1 protein in plasma from the same patients followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…While studies in individuals without CVDs indicated an inverse relationship between omentin and subclinical atherosclerosis [6, 11, 13, 14], studies in patients with established CVDs demonstrated that higher omentin levels were cross-sectionally associated with the severity of coronary artery disease [35, 39] and were longitudinally associated with adverse CVD outcome [40, 41]. Increased plasma omentin levels were also demonstrated after acute cardiac ischemia in patients undergoing cardiac surgery [42]. Importantly, in patients with coronary artery disease and ≥ 90% coronary occlusion, plasma omentin levels were not only increased with the disease severity, but also were independently associated with better collateral circulation, or better endothelial function [39].…”
Section: Discussionmentioning
confidence: 99%
“…While studies in individuals without CVDs indicated an inverse relationship between omentin and subclinical atherosclerosis [6, 11, 13, 14], studies in patients with established CVDs demonstrated that higher omentin levels were cross-sectionally associated with the severity of coronary artery disease [35, 39] and were longitudinally associated with adverse CVD outcome [40, 41]. Increased plasma omentin levels were also demonstrated after acute cardiac ischemia in patients undergoing cardiac surgery [42]. Importantly, in patients with coronary artery disease and ≥ 90% coronary occlusion, plasma omentin levels were not only increased with the disease severity, but also were independently associated with better collateral circulation, or better endothelial function [39].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated the relationship between omentin-1 and coronary artery disease [14,15], stroke, and complications of T2DM [13,16]. Based on these findings, some controversial data emerged about a negative, positive, or independent correlation between omentin-1 levels and cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiomyocytes are sensitive to the changes of microenvironment, especially ischemia. Numerous studies have reported that mRNA transcription and protein expression change during the first 90 minutes of ischemic-reperfusion episode in both human and animals [ 31 , 32 ]. ATP 5G1, which target to mitochondria, can be imported into mitochondria under ischemic conditions [ 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%